MeerKAT uncovers the physics of an odd radio circle. Issue 1 (24th March 2022) - Norris, Ray P; Collier, J D; Crocker, Roland M; Heywood, Ian; Macgregor, Peter; Rudnick, L; Shabala, Stas; Andernach, Heinz; da Cunha, Elisabete; English, Jayanne; Filipović, Miroslav; Koribalski, Bärbel S; et al.
ABSTRACT: Odd radio circles (ORCs) are recently-discovered faint diffuse circles of radio emission, of unknown cause, surrounding galaxies at moderate redshift ( z ∼ 0.2 – 0.6). Here, we present detailed new MeerKAT radio images at 1284 MHz of the first ORC, originally discovered with the Australian Square Kilometre Array Pathfinder, with higher resolution (6 arcsec) and sensitivity (∼ 2.4 μJy/beam). In addition to the new images, which reveal a complex internal structure consisting of multiple arcs, we also present polarization and spectral index maps. Based on these new data, we consider potential mechanisms that may generate the ORCs.